Detrital zircon record of Meso- and Neoproterozoic sedimentary basins in northern part of the Siberian Craton: Characterizing buried crust of the basement - Priyatkina, N.; Khudoley, A.; Collins, William; Kuznetsov, N.; Huang, H. (Elsevier BV, 2016)
We present new LA ICP-MS detrital zircon data from Meso- and Neoproterozoic sedimentary basins located in the northern and western parts of the Siberian Craton. Along the western cratonic margin (Turukhansk Uplift, northern Yenisei Ridge), the basins accumulated predominantly 2.6–2.5 Ga and 1.9–1.85 Ga erosional products, while the main sources for the fill of intracratonic basin to the northeast near the Anabar Shield (East Anabar basin) were 2.9–2.7 Ga and 2.1–1.95 Ga old igneous rocks. The studied Meso- to Early Neoproterozoic sandstones were deposited in rift-related or passive margin settings, and underwent major craton-wide recycling to produce late Ediacaran silicilastic successions. Meso- to Early Neoproterozoic sandstones are immature to submature pointing to erosion of proximal Archean and Paleoproterozoic crustal units. The unique detrital age spectra for the northeast and western basins indicate provinciality and provide a basis for unravelling the age of buried domains of the Siberian Craton basement.